Polyacrylonitrile carbon fiber precursor as well as preparation method and application thereof

By distributing boron and silicon elements radially in the polyacrylonitrile carbon fiber raw filament and controlling their permeability, the problem of low homogenization during pre-oxidation is solved, and high-strength carbon fiber preparation is achieved.

CN119843381APending Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202311353275.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, the polyacrylonitrile carbon fiber protofilament has a low degree of homogenization during the pre-oxidation process, resulting in excessive oxidation of the cortex, which in turn affects the fiber strength.

Method used

By distributing boron elements and silicon elements radially in the polyacrylonitrile carbon fiber protofilament, the degree of permeability and distribution of boron elements are controlled to ensure homogenization of the oxidation reaction. The specific method includes oiling treatment using an oil agent containing boron and silicon compounds in the spinning process, and achieving precise penetration of boron and silicon elements by controlling the oiling time, temperature and pore structure.

Benefits of technology

The homogenization and preoxidation of polyacrylonitrile carbon fiber protofilament is achieved, the tensile properties of carbon fiber are improved, and the strength of carbon fiber reaches ≥6.1GPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843381A_ABST
    Figure CN119843381A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon fiber preparation, and discloses a polyacrylonitrile carbon fiber precursor as well as a preparation method and application thereof. The diameter of the polyacrylonitrile carbon fiber precursor is x microns, the polyacrylonitrile carbon fiber precursor contains boron elements in y microns from outside to inside in the radial direction, and the polyacrylonitrile carbon fiber precursor contains silicon elements in z microns from outside to inside in the radial direction; wherein y / x is equal to 15-45%, and z / x is equal to 5-15%; the content of the boron element at 0.2 y microns from outside to inside in the radial direction is A, the content of the boron element at 0.8 y microns from outside to inside in the radial direction is B, and A / B is larger than or equal to 4.5. The polyacrylonitrile carbon fiber precursor is easy to homogenize and pre-oxidize, and can be used for preparing carbon fibers with excellent tensile properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon fiber preparation, and in particular to a polyacrylonitrile carbon fiber precursor and a preparation method and application thereof. Background Art

[0002] The most widely used process route in this field is to obtain carbon fiber by oxidation and carbonization of polyacrylonitrile fiber. At the same time, the use of polyacrylonitrile-based carbon fiber accounts for more than 90% of the world's total carbon fiber consumption. The production process of polyacrylonitrile-based fiber is very long, and each link is closely linked and the previous and subsequent processes affect each other. To obtain high-quality carbon fiber, each process link must match each other and be continuously optimized. The core indicator of carbon fiber quality is strength. Higher-strength carbon fiber has a wider range of applications. Fields such as aerospace and hydrogen storage cylinders have high requirements for carbon fiber strength. The current actual strength of carbon fiber is less than 5% of the theoretical strength. There are still many blind spots in both basic principles and existing processes.

[0003] Carbon fiber is obtained by oxidizing and carbonizing polyacrylonitrile fiber, so obtaining polyacrylonitrile fiber that is easy to homogenize and pre-oxidize is an important link in the production process. The production routes of polyacrylonitrile carbon fiber precursor can be divided into two main types based on the process, one is wet spinning and the other is dry-jet wet spinning. The two have different technical characteristics, and the application fields of the carbon fiber finally obtained are also different. The dry-wet method refers to a spinning method in which a thin stream of the stock solution is sprayed into the air and then coagulated. The dry-wet method can obtain precursors with fewer defects and smooth surfaces. It has been reported that high-strength carbon fibers can be obtained through the dry-wet process.

[0004] However, the process characteristics of the dry and wet methods have also brought new challenges to the subsequent oxidation and carbonization. In the production process of carbon fiber, the pre-oxidation process is also another important process in the production of carbon fiber. During the pre-oxidation process, polyacrylonitrile reacts under certain conditions and gradually forms a heat-resistant trapezoidal structure. This process involves both cyclization and oxidation reactions. How to balance the relationship between the two so that the pre-oxidized fiber has a uniform and thick cortical structure is one of the core issues in the preparation of high-performance carbon fibers. The rate of the cyclization reaction of polyacrylonitrile initiated by acidic monomers is mainly determined by the copolymer components and the reaction temperature, while the oxidation reaction is controlled by diffusion factors. During the pre-oxidation process, if the mass transfer resistance of the fiber cortex is large, it may cause a large difference in the degree of oxidation reaction along the radial direction inside the fiber. In particular, the precursor obtained by the dry and wet process has a small specific surface area, high density, and lack of pores. The mass transfer resistance of oxygen in the fiber is greater, which makes it easy to peroxidize near the cortex, resulting in a decrease in fiber strength.

[0005] To alleviate this phenomenon, patent applications 201210271045.3, 201010286160.9, 201810445237.9, JP60092349A, JP2020172595A and JP1999124744A proposed the use of boron compounds as inhibitors of oxidation reactions during pre-oxidation to improve the uniformity of the pre-oxidation process. The principle is to use boron compounds to hinder the oxidation process of the cortex and provide time for the internal pre-oxidation process. Among them, the solution proposed by patent applications CN201210271045.3 and CN201010286160.9 is to impregnate boron compounds after the precursor is formed. This method is relatively convenient to operate, but the finished fiber has completed the densification process, so it is difficult for boron to enter the fiber and can only be enriched in the outermost layer, so it has limited effect on alleviating the skin-core structure caused by pre-oxidation. Patent applications JP60092349A and 201810445237.9 propose to add nano-sized borides to the stock solution to improve the formation of the skin-core structure during the pre-oxidation process, but the pre-oxidation delay effect of the borides can only be better exerted due to molecular-level mixing, and this mixed system is difficult to be completely uniform. When the additives agglomerate, new defects will be introduced to reduce the fiber performance. Patent application JP2020172595A proposes to use boron-containing vinyl monomers for copolymerization to improve the performance of carbon fibers, but since there is no gradient distribution of boron in such methods, the effect is not significant. Patent application JP1999124744A proposes to control the swelling degree of the precursor to within 100% before oiling, and to inhibit inward penetration with a silicone oil agent, and proposes to add a boron-containing compound to the oil agent to achieve the purpose of preparing high-quality carbon fiber precursors, but the technical solution does not mention a method for controlling the penetration depth of boron.

[0006] The key to achieving homogenized pre-oxidation is to reasonably arrange the time for the inner and outer layers to complete pre-oxidation. When the fiber structure is not optimized, the reaction is limited by the diffusion efficiency, and it is very easy for the inner layer to not react when the outer layer oxidation is basically completed. This ultimately leads to a large structural difference and causes a loss of fiber strength. To eliminate this radial difference, it is necessary to reasonably design the radial reaction characteristics of the fiber. Currently, regulating the reaction performance by the content of boron compounds is a more feasible means. However, although there have been application cases of borides in the prior art, no more effective control method has been given. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems of low homogenization degree and easy over-oxidation of the cortex during the pre-oxidation process of polyacrylonitrile carbon fiber precursor in the prior art, and to provide a polyacrylonitrile carbon fiber precursor and a preparation method and application thereof.

[0008] In order to achieve the above object, the present invention provides a polyacrylonitrile carbon fiber precursor, wherein the diameter of the polyacrylonitrile carbon fiber precursor is x microns, and the boron element is contained within y microns from the outside to the inside in the radial direction, and the silicon element is contained within z microns from the outside to the inside in the radial direction; wherein y / x=15-45%, z / x=5-15%;

[0009] The content of boron element at 0.2y microns from the outside to the inside along the radial direction is A, and the content of boron element at 0.8y microns from the outside to the inside along the radial direction is B, and A / B≥4.5.

[0010] Preferably, the raw material for preparing the polyacrylonitrile carbon fiber precursor contains a polyacrylonitrile copolymer, and the content of acrylonitrile structural units in the polyacrylonitrile copolymer is ≥95% by weight.

[0011] Preferably, 8≤x≤14;

[0012] Preferably, 1≤y≤6;

[0013] Preferably, 1≤z≤2.5.

[0014] A second aspect of the present invention provides a method for preparing polyacrylonitrile carbon fiber precursor, using a dry-wet spinning process, comprising the following steps:

[0015] (1) subjecting the spinning solution to sequential spinning, coagulation and drawing to obtain hot drawn fibers;

[0016] (2) washing, oiling, drying and steam drawing the heat-drawn fibers in sequence;

[0017] Wherein, the average pore size of the heat-drawn fiber is 6-13nm;

[0018] The oiling conditions include: the oiling immersion time is 1-4s; the oiling immersion temperature is 20-35°C; the oil contains boron compounds and silicon compounds, and the weight ratio of boron element to silicon element in the oil is 1:2-80.

[0019] Preferably, the spinning solution contains polyacrylonitrile copolymer and solvent;

[0020] Preferably, the content of polyacrylonitrile copolymer in the spinning solution is 15-25% by weight;

[0021] Preferably, the viscosity average molecular weight of the polypropylene copolymer is 60,000-140,000.

[0022] Preferably, the fineness of the heat-drawn fiber is 1.5-6 Detx.

[0023] Preferably, the boron compound has a structural formula of RB(OH)2;

[0024] Wherein, R is selected from hydroxyl and C1-C5 alkyl.

[0025] Preferably, the total solid content of the oil is 1-3.5 wt %.

[0026] Preferably, the silicon compound is selected from one or more of amino-modified polydimethylsiloxane, epoxy-modified polydimethylsiloxane and polyether-modified polydimethylsiloxane.

[0027] The third aspect of the present invention provides polyacrylonitrile carbon fiber precursor prepared by the method described above.

[0028] A fourth aspect of the present invention provides the use of the polyacrylonitrile carbon fiber precursor described above in the preparation of carbon fiber.

[0029] A fifth aspect of the present invention provides a method for preparing carbon fiber, the method comprising: sequentially subjecting the polyacrylonitrile carbon fiber precursor described above to pre-oxidation, low-temperature carbonization, and high-temperature carbonization.

[0030] Compared with the prior art, this application has the following beneficial effects:

[0031] 1. The present invention provides a polyacrylonitrile carbon fiber precursor, which is easy to achieve homogenization pre-oxidation and can be used to prepare carbon fibers with excellent tensile properties. The tensile strength of the carbon fibers prepared using the precursor is ≥6.1 GPa.

[0032] 2. In the polyacrylonitrile carbon fiber precursor of the present invention, the boron element has a certain degree of penetration and there is a concentration gradient difference in the radial direction inside the fiber. The boron concentration near the cortex is higher than that on the inside, so the reaction rate gradually accelerates along the radial direction during the oxidation reaction. Therefore, the precursor is easier to achieve homogenization in the pre-oxidation process;

[0033] 3. In the method described in the present invention, by controlling the pore structure of the fiber during the oiling process, the process conditions during the oiling process and the oil composition, the penetration of boron in the polyacrylonitrile carbon fiber precursor is accurately controlled, which is beneficial to achieve homogenization of the pre-oxidation process to obtain carbon fiber with high tensile strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a SEM image of the polyacrylonitrile carbon fiber precursor obtained in Example 2. DETAILED DESCRIPTION

[0035] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0036] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0037] The inventors of the present invention found during the research process that the key to achieving homogenized pre-oxidation is to eliminate the difference in the degree of reaction of the skin and core layers caused by diffusion control, and to reasonably arrange the time required for the inner and outer layers to complete pre-oxidation. When the fiber structure is not optimized, the reaction is limited by the diffusion efficiency, and it is very easy for the inner layer to not react when the outer layer oxidation is basically completed, which ultimately leads to large differences in the radial structure of the pre-oxidized fiber, causing a loss of fiber strength. To eliminate this radial difference, it is necessary to reasonably design the reaction characteristics of the fiber along the radial direction. Based on this, the inventors achieved homogenization of the pre-oxidation process by controlling the penetration degree and distribution characteristics of the boron element in the raw silk, and completed the present invention.

[0038] On one hand, the present invention provides a polyacrylonitrile carbon fiber precursor, wherein the diameter of the polyacrylonitrile carbon fiber precursor is x microns, and the boron element is contained within y microns from the outside to the inside in the radial direction, and the silicon element is contained within z microns from the outside to the inside in the radial direction; wherein y / x=15-45%, z / x=5-15%;

[0039] The content of boron element at 0.2y microns from the outside to the inside along the radial direction is A, and the content of boron element at 0.8y microns from the outside to the inside along the radial direction is B, and A / B≥4.5.

[0040] In the polyacrylonitrile carbon fiber precursor of the present invention, the boron element is contained within y microns from the outside to the inside in the radial direction, that is, the penetration distance of the boron element in the precursor from the outside to the inside in the radial direction is y microns, and y / x represents the penetration degree of the boron element in the precursor; the silicon element is contained within z microns from the outside to the inside in the radial direction, that is, the penetration distance of the silicon element in the precursor from the outside to the inside in the radial direction is z microns, and z / x represents the penetration degree of the silicon element in the precursor. A / B represents the distribution of the content of the boron element in the precursor, and the larger the value of A / B, the larger the proportion of the boron element in the area close to the epidermis of the precursor.

[0041] The present invention precisely limits the penetration degree of boron and silicon in the polyacrylonitrile carbon fiber precursor, and limits the distribution of boron in the precursor. The penetration degree of boron in the precursor is high, and there is a concentration gradient difference of boron in the precursor along the radial direction. The concentration of boron near the cortex is higher than that on the inside, so the reaction rate in this part of the oxidation reaction is the slowest, which is conducive to the homogenization of the pre-oxidation process. At the same time, the silicon element has a low penetration degree, which avoids the adverse effect of excessive penetration of silicon on the strength of carbon fiber.

[0042] In a preferred embodiment, the raw material for preparing the polyacrylonitrile carbon fiber precursor contains a polyacrylonitrile copolymer, and the content of acrylonitrile structural units in the polyacrylonitrile copolymer is ≥95% by weight. Further preferably, the polyacrylonitrile copolymer also contains a second monomer structural unit, and the second monomer is selected from monomers containing vinyl groups, such as itaconic acid or methyl methacrylate.

[0043] In a preferred embodiment, 8≤x≤14. Specifically, the value of x can be 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5 or 14.

[0044] In a preferred embodiment, 1≤y≤6, more preferably 2≤y≤4. Specifically, the value of y can be 2, 2.5, 2.77, 3, 3.21, 3.44, 3.5 or 4.

[0045] In a preferred embodiment, 1≤z≤2.5, more preferably 1≤z≤2. Specifically, the value of z may be 1, 1.1, 1.2, 1.125, 1.3, 1.5, 1.6, 1.8, 2 or 2.5.

[0046] A second aspect of the present invention provides a method for preparing polyacrylonitrile carbon fiber precursor, using a dry-wet spinning process, comprising the following steps:

[0047] (1) subjecting the spinning solution to sequential spinning, coagulation and drawing to obtain hot drawn fibers;

[0048] (2) washing, oiling, drying and steam drawing the heat-drawn fibers in sequence;

[0049] Wherein, the average pore size of the heat-drawn fiber is 6-13 nm, preferably 8-12 nm;

[0050] The oiling conditions include: the oiling immersion time is 1-4s, preferably 2-3s; the oiling immersion temperature is 20-35°C; the oil agent used contains boron compounds and silicon compounds, and the weight ratio of boron element to silicon element in the oil agent is 1:2-80, preferably 1:4-40.

[0051] In a specific embodiment, the weight ratio of boron to silicon in the oil can be 1:4, 1:5, 1:8, 1:9, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35 or 1:40.

[0052] In a preferred embodiment, the oiling immersion temperature during the oiling is 26-34°C, and can be specifically 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 33°C or 34°C.

[0053] In order to achieve reasonable control of boron and silicon in the precursor, in the method described in the present invention, the wet fiber precursor is oiled with an oil containing boron, so that the boron element can enter the fiber. However, if the boron element is added in the oiling process, the penetration of the boride is accompanied by excessive penetration of the silicone-containing oil, which will lead to the subsequent generation of more silicon carbide defects inside the fiber, thereby causing the carbon fiber to lose strength. Therefore, the method described in the present invention achieves precise control of the penetration of boron and silicon elements by reasonably controlling the conditions such as the pore structure, oiling temperature and residence time of the fiber precursor during oiling. The boron element in the obtained precursor has a high degree of penetration and there is a certain concentration gradient in the radial direction of the precursor, which can achieve homogenization of the pre-oxidation process; at the same time, the penetration degree of the silicon element is relatively low, which effectively reduces the generation of silicon carbide inside the fiber and reduces the adverse effects on the fiber strength.

[0054] In specific embodiments, the average pore size of the heat-drawn fiber can be 8 nm, 8.5 nm, 9 nm, 9.5 nm, 10 nm, 10.2 nm, 10.5 nm, 10.7 nm, 10.8 nm, 11 nm, 11.1 nm, 11.5 nm or 12 nm.

[0055] In a preferred embodiment, the fineness of the heat-drawn fiber is 1.5-6 Detx.

[0056] In a preferred embodiment, the spinning solution contains a polyacrylonitrile copolymer and a solvent.

[0057] In a preferred embodiment, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is ≥ 95% by weight.

[0058] Further preferably, the polyacrylonitrile copolymer is obtained by copolymerizing acrylonitrile and a second monomer. Preferably, the second monomer is selected from vinyl monomers.

[0059] Further preferably, the second monomer is selected from itaconic acid or methyl methacrylate.

[0060] In a specific embodiment, in the polyacrylonitrile copolymer, the content of the acrylonitrile structural unit is 95-99.4% by weight, and the content of the second monomer structural unit is 0.6-5% by weight.

[0061] In a preferred embodiment, the content of the polyacrylonitrile copolymer in the spinning solution is 15-25% by weight, and specifically, it may be 15%, 16%, 17%, 18%, 19%, 20%, 20.5%, 21%, 22%, 23%, 24% or 25% by weight.

[0062] In a preferred embodiment, the solvent is dimethyl sulfoxide.

[0063] In a preferred embodiment, the viscosity average molecular weight of the polypropylene copolymer is 60,000-140,000. Specifically, it can be 60,000, 70,000, 75,000, 79,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000 or 160,000.

[0064] In a specific embodiment, when the second monomer is selected from an acidic monomer such as itaconic acid, before the spinning solution is spun, the method further comprises a step of treating the spinning solution with ammonia gas, which can neutralize the carboxyl groups in itaconic acid.

[0065] In a preferred embodiment, the spinneret used in the spinning has an aperture of 0.1-0.15 mm and a hole number of 4k.

[0066] In a preferred embodiment, the coagulation is carried out in a coagulation bath, which is a dimethyl sulfoxide aqueous solution with a concentration of 25-35% by weight, and the temperature of the coagulation bath is 0-15°C.

[0067] In a preferred embodiment, the water washing temperature is 40-70°C.

[0068] In the method described in the present invention, in order to better control the penetration degree and distribution of boron elements, in a preferred embodiment, the structural formula of the boron compound is RB(OH)2; wherein R is selected from hydroxyl group and C1-C5 alkyl group.

[0069] More preferably, R is selected from methyl, ethyl or hydroxy.

[0070] In a specific embodiment, the boron compound is selected from boric acid, methylboric acid or ethylboric acid.

[0071] In a preferred embodiment, the silicon compound is selected from one or more of amino-modified polydimethylsiloxane, epoxy-modified polydimethylsiloxane and polyether-modified polydimethylsiloxane.

[0072] In the present invention, the total solid content of the oil agent refers to the total content of all non-volatile components in the oil agent including boron compounds and silicon compounds. There is no special requirement for other components in the oil agent except boron compounds and silicon compounds, and they can be selected conventionally in the art.

[0073] Preferably, the total solid content of the oil is 1-3.5 wt %.

[0074] In a specific embodiment, the drying temperature may be 150°C.

[0075] In a preferred embodiment, the steam pressure during the steam stretching is 3.2-5.4 kg.

[0076] In the present invention, the penetration distance of the boron element (y value) and the penetration distance of the silicon element (z value) can be detected by the following method: the raw silk is embedded with epoxy resin and sliced, and then analyzed using the EDS built into the TEM. The distance from the cortex to the position where the element cannot be detected at the detection limit is the penetration distance of the element.

[0077] In the present invention, the boron content at 0.2 μm from the outside to the inside in the radial direction is A and the boron content at 0.8 μm from the outside to the inside in the radial direction is B. The following method is used to detect: EDS mapping scanning is performed under a scanning electron microscope to obtain a distribution map of the boron element, and image processing software is used to perform ring integration on the pixel points to obtain the distribution concentration.

[0078] The third aspect of the present invention provides polyacrylonitrile carbon fiber precursor prepared by the method described above.

[0079] A fourth aspect of the present invention provides the use of the polyacrylonitrile carbon fiber precursor described above in the preparation of carbon fiber.

[0080] A fifth aspect of the present invention provides a method for preparing carbon fiber, the method comprising: sequentially subjecting the polyacrylonitrile carbon fiber precursor described above to pre-oxidation, low-temperature carbonization, and high-temperature carbonization.

[0081] In a preferred embodiment, the pre-oxidation temperature is 230-270°C.

[0082] In a preferred embodiment, the temperature of the low-temperature carbonization is 475-750°C; specifically, it can be 475°C, 500°C, 550°C, 600°C, 650°C, 700°C or 750°C.

[0083] In a preferred embodiment, the high temperature carbonization temperature is 1100-1550°C.

[0084] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0085] The characterization and testing methods used in the following examples and comparative examples are as follows:

[0086] 1. The fiber diameter is measured by scanning electron microscopy using the fiber diameter test method described in GB / T 3364-2008.

[0087] 2. The method for determining the average pore size of heat-drawn fibers is as follows: the fibers are washed with deionized water at 30°C until the residual DMSO is less than 20 ppm, then immersed in liquid nitrogen, and then freeze-dried at 0.1 Pa and -70°C to obtain a sample, which is then tested using the BET method and the average pore size is obtained according to the BJH method.

[0088] 3. The method for determining the penetration depth of B and Si is as follows: the raw silk is embedded in epoxy resin and sliced, and then analyzed using the EDS built into the TEM. The distance from the cortex to the position where the element cannot be detected at the detection limit is the penetration depth of the element.

[0089] 4. The detection method of the boron content at 0.2y microns from the outside to the inside in the radial direction as A and the boron content at 0.8y microns from the outside to the inside in the radial direction as B is as follows: perform EDS mapping scanning under a scanning electron microscope to obtain a distribution map of the boron element, and use image processing software to perform ring integration on the pixel points to obtain the distribution concentration.

[0090] 5. The carbon fiber tensile strength test method shall refer to the method described in GB / T 336-2005.

[0091] Example 1

[0092] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with a hole number of 4k and a hole diameter of 0.1 mm) to obtain a nascent fiber, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fiber is stretched 3 times at 85°C to obtain a hot stretched fiber with an average fiber pore diameter of 10.8 nm;

[0093] (2) The hot drawn fiber is washed with water and then immersed in an oil agent for treatment, the oil immersion time is 2s and the temperature is 20°C; the oil agent contains 1.6% by weight of amino-modified polydimethylsiloxane and 0.4% by weight of boric acid, the total solid content of the oil agent is 2% by weight, and the weight ratio of boron element to silicon element in the oil agent is 1:9.89; then it is dried and densified at 150°C; then it is stretched under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor is 3.21 μm, the penetration distance of Si is 1.1 μm, and the content distribution of boron element in the precursor is A / B=6.

[0094] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C, and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 6.7 GPa.

[0095] Example 2

[0096] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with 4k holes and a pore size of 0.1 mm) to obtain nascent fibers, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0° C. The nascent fibers are drawn 3 times at 85° C. to obtain hot-drawn fibers with an average pore size of 10.8 nm;

[0097] (2) The hot drawn fiber was washed with water and then immersed in an oil agent for treatment, the oil immersion time was 2s and the temperature was 20°C; the oil agent contained 1.6 wt% of amino-modified polydimethylsiloxane and 0.4 wt% of methylboric acid, the total solid content of the oil agent was 2 wt%, and the weight ratio of boron element to silicon element in the oil agent was 1:9.57; then the fiber was dried and densified at 150°C; then the fiber was drawn under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor was 2.95 μm, the penetration distance of Si was 1.1 μm, and the content distribution of boron element in the precursor was A / B=5.5; the SEM image of the precursor is as follows Figure 1 shown.

[0098] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C, and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 6.5 GPa.

[0099] Example 3

[0100] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight of acrylonitrile, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath onto nascent fibers through a spinneret (with 4k holes and a pore size of 0.1 mm), wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0° C. The nascent fibers are drawn 3 times at 85° C. to obtain heat-drawn fibers with an average pore size of 10.8 nm;

[0101] (2) The hot drawn fiber was washed with water and then immersed in an oil agent for treatment, the oil immersion time was 2s and the temperature was 20°C; the oil agent contained 1.6 wt% of amino-modified polydimethylsiloxane and 0.4 wt% of ethylboric acid, the total solid content of the oil agent was 2 wt%, and the weight ratio of boron element to silicon element in the oil agent was 1:11.82; then the fiber was dried and densified at 150°C; then the fiber was drawn under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor was 2.21 μm, the penetration distance of Si was 1.1 μm, and the content distribution of boron element in the precursor was A / B=4.6.

[0102] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C, and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 6.2 GPa.

[0103] Example 4

[0104] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with a hole number of 4k and a hole diameter of 0.1 mm) to obtain a nascent fiber, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fiber is stretched 3.5 times at 85°C to obtain a hot stretched fiber with an average pore diameter of 10.2 nm;

[0105] (2) The hot drawn fiber was washed with water and then immersed in an oil agent for treatment, the oil immersion time was 2s and the temperature was 20°C; the oil agent contained 1.6 wt% of amino-modified polydimethylsiloxane and 0.4 wt% of boric acid, the total solid content of the oil agent was 2 wt%, and the weight ratio of boron element to silicon element in the oil agent was 1:9.89; then the fiber was dried and densified at 150°C; then the fiber was drawn under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile carbon fiber precursor with a diameter of 9 μm; after testing, the B penetration distance in the precursor was 2.77 μm, the Si penetration distance was 1.25 μm, and the content distribution of the boron element in the precursor was A / B=6.5.

[0106] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C, and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 6.2 GPa.

[0107] Example 5

[0108] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with 4k holes and a pore size of 0.1 mm) to obtain nascent fibers, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0° C. The nascent fibers are drawn 3 times at 85° C. to obtain hot-drawn fibers with an average pore size of 11.1 nm;

[0109] (2) The hot drawn fiber was washed with water and then immersed in an oil agent for treatment, the oil immersion time was 2s and the temperature was 20°C; the oil agent contained 1.6 wt% of amino-modified polydimethylsiloxane and 0.4 wt% of boric acid, the total solid content of the oil agent was 2 wt%, and the weight ratio of boron element to silicon element in the oil agent was 1:9.89; then the fiber was dried and densified at 150°C; then the fiber was drawn under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile carbon fiber precursor with a diameter of 11 μm; after testing, the penetration distance of B in the precursor was 3.98 μm, the penetration distance of Si was 1.44 μm, and the content distribution of boron element in the precursor was A / B=7.1.

[0110] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C, and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 6.2 GPa.

[0111] Example 6

[0112] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with 4k holes and a pore size of 0.1 mm) to obtain nascent fibers, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fibers are drawn 3 times at 85°C to obtain hot-drawn fibers with an average pore size of 10.7 nm;

[0113] (2) The hot drawn fiber was washed with water and then immersed in an oil agent for treatment, the oil immersion time was 2s and the temperature was 20°C; the oil agent contained 1.6 wt% of amino-modified polydimethylsiloxane and 0.4 wt% of boric acid, the total solid content of the oil agent was 2 wt%, and the weight ratio of boron element to silicon element in the oil agent was 1:89. Then, it was dried and densified at 150°C; then, it was stretched under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile carbon fiber precursor with a diameter of 9.5 μm; after testing, the penetration distance of B in the precursor was 3.44 μm, the penetration distance of Si was 1.04 μm, and the content distribution of boron element in the precursor was A / B=6.1.

[0114] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C, and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 6.6 GPa.

[0115] Example 7

[0116] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with a hole number of 4k and a hole diameter of 0.1 mm) to obtain a nascent fiber, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fiber is stretched 3 times at 85°C to obtain a hot stretched fiber with an average fiber pore diameter of 10.8 nm;

[0117] (2) The hot drawn fiber is washed with water and then immersed in an oil agent for treatment, the oil immersion time is 3s, and the temperature is 20°C; the oil agent contains 1.6% by weight of amino-modified polydimethylsiloxane and 0.4% by weight of boric acid, the total solid content of the oil agent is 2% by weight, and the weight ratio of boron element to silicon element in the oil agent is 1:9.89; then it is dried and densified at 150°C; then it is stretched under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor is 3.62 μm, the penetration distance of Si is 1.21 μm, and the content distribution of boron element in the precursor is A / B=5.5.

[0118] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C, and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 6.5 GPa.

[0119] Example 8

[0120] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with a hole number of 4k and a hole diameter of 0.1 mm) to obtain a nascent fiber, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fiber is stretched 3 times at 85°C to obtain a hot stretched fiber with an average fiber pore diameter of 10.8 nm;

[0121] (2) The hot drawn fiber is washed with water and then immersed in an oil agent for treatment, the oil immersion time is 2s and the temperature is 25°C; the oil agent contains 1.6% by weight of amino-modified polydimethylsiloxane and 0.4% by weight of boric acid, the total solid content of the oil agent is 2% by weight, and the weight ratio of boron element to silicon element in the oil agent is 1:9.89; then it is dried and densified at 150°C, and then stretched under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile-based carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor is 3.55 μm, the penetration distance of Si is 1.15 μm, and the content distribution of boron element in the precursor is A / B=5.9.

[0122] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, carbonized at 900°C, carbonized at 1250°C and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 6.2 GPa.

[0123] Example 9

[0124] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with a hole number of 4k and a hole diameter of 0.1 mm) to obtain a nascent fiber, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fiber is stretched 3 times at 85°C to obtain a hot stretched fiber with an average fiber pore diameter of 10.8 nm;

[0125] (2) The hot drawn fiber was washed with water and then immersed in an oil agent for treatment, the oil immersion time was 2s and the temperature was 20°C; the oil agent contained 1.28 wt% of amino-modified polydimethylsiloxane and 0.32 wt% of boric acid, the total solid content of the oil agent was 1.6 wt%, and the weight ratio of boron element to silicon element in the oil agent was 1:9.89; then the fiber was dried and densified at 150°C; then the fiber was drawn under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor was 2.82 μm, the penetration distance of Si was 1.01 μm, and the content distribution of boron element in the precursor was A / B=6.1.

[0126] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C, and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 6.1 GPa.

[0127] Comparative Example 1

[0128] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with 4k holes and a pore size of 0.1 mm) to obtain nascent fibers, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0° C. The nascent fibers are drawn 3 times at 85° C. to obtain hot-drawn fibers with an average pore size of 11.1 nm;

[0129] (2) The hot drawn fiber was washed with water and then immersed in an oil agent for treatment, the oil immersion time was 2s and the temperature was 20°C; the oil agent contained 1.6 wt% of amino-modified polydimethylsiloxane and 0.4 wt% of boric acid, the total solid content of the oil agent was 2 wt%, and the weight ratio of boron element to silicon element in the oil agent was 1:9.89; then the fiber was dried and densified at 150°C; then the fiber was drawn under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile carbon fiber precursor with a diameter of 8 μm; after testing, the B penetration distance in the precursor was 4 μm, the Si penetration distance was 1.26 μm, and the content distribution of the boron element in the precursor was A / B=5.5.

[0130] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 5.9 GPa.

[0131] Comparative Example 2

[0132] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with 4k holes and a pore size of 0.1 mm) to obtain a nascent fiber, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fiber is drawn 4 times at 90°C to obtain a hot-drawn fiber with an average pore size of 9.1 nm;

[0133] (2) The hot drawn fiber is washed with water and then immersed in an oil agent for treatment, the oil immersion time is 2s and the temperature is 20°C; the oil agent contains 1.6% by weight of amino-modified polydimethylsiloxane and 0.4% by weight of boric acid, the total solid content of the oil agent is 2% by weight, and the weight ratio of boron element to silicon element in the oil agent is 1:9.89; then it is dried and densified at 150°C; then it is stretched under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile-based carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor is 2.42 μm, the penetration distance of Si is 0.48 μm, and the content distribution of boron element in the precursor is A / B=3.35.

[0134] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 5.7 GPa.

[0135] Comparative Example 3

[0136] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with a hole number of 4k and a hole diameter of 0.1 mm) to obtain a nascent fiber, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fiber is stretched 3 times at 85°C to obtain a hot stretched fiber with an average fiber pore diameter of 10.8 nm;

[0137] (2) The hot drawn fiber was washed with water and then immersed in an oil agent for treatment, the oil immersion time was 8 seconds and the temperature was 20°C; the oil agent contained 1.6 weight % of amino-modified polydimethylsiloxane and 0.4 weight % of boric acid, the total solid content of the oil agent was 2 weight %, and the weight ratio of boron element to silicon element in the oil agent was 1:9.89; then the fiber was dried and densified at 150°C; then the fiber was drawn under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile-based carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor was 5.0 μm, the penetration distance of Si was 1.07 μm, and the content distribution of boron element in the precursor was A / B=6.6.

[0138] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 5.9 GPa.

[0139] Comparative Example 4

[0140] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with a hole number of 4k and a hole diameter of 0.1 mm) to obtain a nascent fiber, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fiber is stretched 3 times at 85°C to obtain a hot stretched fiber with an average fiber pore diameter of 10.8 nm;

[0141] (2) The hot drawn fiber is washed with water and then immersed in an oil agent for treatment, the oil immersion time is 0.5s, and the temperature is 20°C; the oil agent contains 1.6% by weight of amino-modified polydimethylsiloxane and 0.4% by weight of boric acid, the total solid content of the oil agent is 2% by weight, and the weight ratio of boron element to silicon element in the oil agent is 1:9.89; then it is dried and densified at 150°C; then it is stretched under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile-based carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor is 0.88 μm, the penetration distance of Si is 0.43 μm, and the content distribution of boron element in the precursor is A / B=2.1.

[0142] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 5.4 GPa.

[0143] Comparative Example 5

[0144] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with a hole number of 4k and a hole diameter of 0.1 mm) to obtain a nascent fiber, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fiber is stretched 3 times at 85°C to obtain a hot stretched fiber with an average fiber pore diameter of 10.8 nm;

[0145] (2) The hot drawn fiber was washed with water and then immersed in an oil agent for treatment, the oil immersion time was 2s and the temperature was 20°C; the oil agent contained 1.6 wt% of amino-modified polydimethylsiloxane and 0.4 wt% of anthracene boric acid, the total solid content of the oil agent was 2 wt%, and the weight ratio of boron element to silicon element in the oil agent was 1:35.52; then the fiber was dried and densified at 150°C; then the fiber was drawn under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile-based carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor was 0.81 μm, the penetration distance of Si was 1.1 μm, and the content distribution of boron element in the precursor was A / B=1.8.

[0146] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 230-260°C, then carbonized at 700°C, then carbonized at 1250°C and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 5.1 GPa.

[0147] Comparative Example 6

[0148] (1) The spinning stock solution is a dimethyl sulfoxide solution of a polyacrylonitrile copolymer, wherein the content of the polyacrylonitrile copolymer is 20.5% by weight, the viscosity-average molecular weight of the polyacrylonitrile copolymer is 79,000, the content of acrylonitrile structural units in the polyacrylonitrile copolymer is 98.5% by weight, the content of itaconic acid structural units is 1.5% by weight, and the carboxyl groups in the itaconic acid are neutralized by ammonia before spinning; the spinning stock solution is sprayed into a coagulation bath through a spinneret (with a hole number of 4k and a hole diameter of 0.1 mm) to obtain a nascent fiber, wherein the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25% by weight and the coagulation bath temperature is 0°C; the nascent fiber is stretched 3 times at 85°C to obtain a hot stretched fiber with an average fiber pore diameter of 10.8 nm;

[0149] (2) The hot drawn fiber is washed with water and then immersed in an oil agent for treatment, the oil immersion time is 2 seconds and the temperature is 40°C; the oil agent contains 1.6 weight % of amino-modified polydimethylsiloxane and 0.4 weight % of boric acid, the total solid content of the oil agent is 2 weight %, and the weight ratio of boron element to silicon element in the oil agent is 1:9.4; then it is dried and densified at 150°C; then it is stretched under a steam pressure of 4.0 kg to finally obtain a polyacrylonitrile-based carbon fiber precursor with a diameter of 10 μm; after testing, the penetration distance of B in the precursor is 4.8 μm, the penetration distance of Si is 1.8 μm, and the content distribution of boron element in the precursor is A / B=1.8.

[0150] The polyacrylonitrile carbon fiber precursor was pre-oxidized at 250°C, then carbonized at 700°C, then carbonized at 1250°C and coated with an epoxy sizing agent to obtain a carbon fiber tow. The final carbon fiber multifilament had a tensile strength of 4.8 GPa.

[0151] Test Example 1

[0152] The penetration distance (y) and penetration degree (y / x) of B in the carbon fiber precursor, the penetration distance (z) and penetration degree (z / x) of Si, and the diameter (x) of the carbon fiber precursor in the embodiments and comparative examples are shown in Table 1, and the content distribution of boron in the precursor (A / B) and the tensile strength of the carbon fiber are shown in Table 2.

[0153] Table 1

[0154]

[0155] Table 2

[0156] A / B Tensile strength(GPa) Example 1 6 6.7 Example 2 5.5 6.5 Example 3 4.6 6.2 Example 4 6.5 6.2 Example 5 7.1 6.2 Example 6 6.1 6.6 Example 7 5.5 6.5 Example 8 5.9 6.2 Example 9 6.1 6.1 Comparative Example 1 5.5 5.9 Comparative Example 2 3.35 5.7 Comparative Example 3 6.6 5.9 Comparative Example 4 2.1 5.4 Comparative Example 5 1.8 5.1 Comparative Example 6 1.8 4.8

[0157] It can be seen from Table 1 and Table 2 that the carbon fiber precursor described in the present invention is easy to achieve homogenization pre-oxidation and can be used to prepare carbon fiber with extremely excellent tensile properties.

[0158] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polyacrylonitrile carbon fiber precursor, characterized in that: The diameter of the polyacrylonitrile carbon fiber precursor is x microns, and the boron element is contained within y microns from the outside to the inside in the radial direction, and the silicon element is contained within z microns from the outside to the inside in the radial direction; wherein y / x=15-45%, z / x=5-15%; The content of boron element at 0.2y microns from the outside to the inside along the radial direction is A, and the content of boron element at 0.8y microns from the outside to the inside along the radial direction is B, and A / B≥4.

5.

2. The polyacrylonitrile carbon fiber precursor according to claim 1, characterized in that: The raw material for preparing the polyacrylonitrile carbon fiber precursor contains a polyacrylonitrile copolymer, and the content of acrylonitrile structural units in the polyacrylonitrile copolymer is ≥95% by weight.

3. The polyacrylonitrile carbon fiber precursor according to claim 1 or 2, characterized in that: 8≤x≤14; Preferably, 1≤y≤6; Preferably, 1≤z≤2.

5.

4. A method for preparing polyacrylonitrile carbon fiber precursor, characterized in that: The dry-wet spinning process includes the following steps: (1) subjecting the spinning solution to sequential spinning, coagulation and drawing to obtain hot drawn fibers; (2) washing, oiling, drying and steam drawing the heat-drawn fibers in sequence; Wherein, the average pore size of the heat-drawn fiber is 6-13nm; The oiling conditions include: the oiling immersion time is 1-4s; the oiling immersion temperature is 20-35°C; the oil contains boron compounds and silicon compounds, and the weight ratio of boron element to silicon element in the oil is 1:2-80.

5. The method according to claim 4, characterized in that The spinning solution contains polyacrylonitrile copolymer and solvent; Preferably, the content of polyacrylonitrile copolymer in the spinning solution is 15-25% by weight; Preferably, the viscosity average molecular weight of the polypropylene copolymer is 60,000-140,000.

6. The method according to claim 4, characterized in that The fineness of the heat-drawn fiber is 1.5-6 Detx.

7. The method according to claim 4 or 5, characterized in that: The structural formula of the boron compound is RB(OH)2; Wherein, R is selected from hydroxyl and C1-C5 alkyl.

8. The method according to any one of claims 4 to 7, characterized in that: The total solid content of the oil is 1-3.5% by weight.

9. The method according to claim 7, characterized in that: The silicon compound is selected from one or more of amino-modified polydimethylsiloxane, epoxy-modified polydimethylsiloxane and polyether-modified polydimethylsiloxane.

10. Polyacrylonitrile carbon fiber precursor prepared by the method according to any one of claims 4 to 9.

11. Use of the polyacrylonitrile carbon fiber precursor according to any one of claims 1 to 3 and 10 in the preparation of carbon fiber.

12. A method for preparing carbon fiber, characterized in that: The method comprises: sequentially subjecting the polyacrylonitrile carbon fiber precursor according to claim 1 or 10 to pre-oxidation, low-temperature carbonization and high-temperature carbonization.

Citation Information

Patent Citations

  • Method for preparing carbon fibers from boron modified polyacrylonitrile precursors

    CN101956252A

  • Polyacrylonitrile-based carbon fibers, their preparation methods and applications

    CN103572411B

  • Preparation method of boron-silica doped carbon fiber with high antioxidation performance

    CN108708000A

  • Molding polyacrylonitrile composition

    JP1985092349A

  • Polyacrylonitrile copolymer, carbon fiber precursor fiber, and method for producing carbon fiber precursor fiber and method for producing carbon fiber

    JP2020172595A